Legal Protection for QRIS Users as an Electronic Payment Tool in Trade Transactions - Luvianti, Teressyavira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Forms of Legal Protection for QRIS Users as Electronic Payment Instruments in Trade Transactions There are two types, the first is preventive legal protection carried out by Bank Indonesia for violations , this is done by means of administrative sanctions in the form of warnings, fines, to temporary suspension of some or even all electronic money activities and sanctions for revocation of e-money operating licenses . Second, through repressive legal protection, namely protection in the form of sanctions in the event of a dispute or criminal act for consumers who misuse the QRIS code. Legal Settlement for QRIS Users Who Experience Losses is carried out by means of litigation, namely through the courts under the Supreme Court, while non-litigation can be carried out at the BPSK institution, Arbitration using non-litigation dispute resolution methods